Selective Increases of Procoagulant Activity in Rabbit Lymphoid Populations In Vitro Following Stimulation with Endotoxin: Dependence on Anatomic Source - McGee, Maria P; Rothberger, Henry; Lee, Tung-Kuang (Thrombosis and Haemostasis, 1984)
Rabbit mononuclear leukocytes isolated from a variety of anatomic sites were examined for ability to generate procoagulant activity in vitro. Marrow, blood and spleen mononuclear cell populations were found to differ functionally from lymph node, thymus and alveolar populations by having much greater ability to increase in tissue factor activity in response to an endotoxin stimulus. Thus, after incubation in the presence of endotoxin, leukocytes obtained from marrow, blood, and spleen were found to increase in procoagulant activity characterized as tissue factor by 832, 1942 and 12.6 fold, respectively. In contrast, pulmonary alveolar macrophages increased in tissue factor activity only by 2.8 fold, and lymph node and thymus mononuclear cells showed little or no increases. These functional differences, demonstrated by exposing the six cell populations to endotoxin under controlled conditions in vitro, likely explain the similar pattern of anatomic selectivity of leukocyte tissue factor increases reported to occur in vivo during endotoxemia and Shwartzman reactions (1).
Keywords: Shwartzman reactions; Leukocyte; Tissue factor activity